Adrenal ganglioneuroma: two case reports and literature review - Gao, Zhenzhou; Qin, Haokai; Li, Bao; Zhao, Hongjun; Zhang, Mingqing (Frontiers in Oncology, 2025)
Adrenal Ganglioneuroma (AGN) is a rare benign tumor that is mostly nonfunctioning and usually presents without significant clinical symptoms. AGN can undergo calcification, but rarely presents with hemorrhage, necrosis, or cystic changes. This article reports two cases of adrenal ganglioneuroma. One patient had normal clinical and biochemical parameters but presented with hypertension; the other patient had elevated cortisol levels and the tumor exhibited liquefactive necrosis, which is extremely rare in AGN. To the best of our knowledge, this is the first report of adrenal ganglioneuroma with simultaneous localized hemangiomatous proliferation and liquefactive necrosis within the tumor. AGN cannot be definitively diagnosed by imaging alone; a pathological examination is required for a final diagnosis. Both patients in this report underwent laparoscopic tumor resection, and their postoperative recovery was satisfactory.